IMPLEMENTASI KEBIJAKAN PERBAIKAN RUMAH DI PERMUKIMAN KUMUH MELALUI PENATAAN KAMPUNG DI DKI JAKARTA PADA TAHUN 2013 (STUDI KASUS: KAMPUNG DERET PETOGOGAN) - Purwati Rahayu Edarsasi; Priyatno Harsasto; D Ghulam Manar (Journal of Politic and Government Studies, 2016)
ABSTRACTThe implementation of house enhancement policy in inhabitable settlement through village structuring at DKI in 2013 (a case study at kampung deret Petogogan) was aimed to find out how a policy is implemented at DKI Jakarta, and how local society’s participation an to changing their house areas healthier, more well-structured and more habitable.The research methodology was qualitative. The data collection came from primary and secondary data. Research subjects were the Department of Housing and Building of DKI Jakarta Province, the Department of Housing and Building of South Jakarta, and Petogogan inhabitants.Tecnique of collecting data, by interview and documentation.The inhabitable is one of the social problems that is difficult to be solved. Building an inhabitable settlement called as slum area can cause a potential problem in the city. The implementation of house enhancement policy in inhabitable settlement through village structuring at DKI Jakarta is one of the outstanding programs planned and socialized by the government of DKI Jakarta. The target village operates the concept of changing regions into one unified region. It is different from the slum reduction programs initiated by the previous governor of Jakarta, the policy involved the community during implementation. Therefore, inhabitants participation is greatly influency of success of the implementation.Key words : Inhabitable Settlement, Policy of Implementation of Enhancement Fund, and Village Structuring